PEMETAAN POTENSI BENCANA ALAM (GEO-DISASTER) AKIBAT PENAMBANGAN BIJIH TIMAH DI KECAMATAN JEBUS DAN PARIT TIGA, KABUPATEN BANGKA BARAT - Fachrudin, Irvani (PROMINE, 2013)
ABSTRACTThe study area is a tin mining region in hundred years, located in Jebus and ParitTiga District, West Bangka Regency, Bangka Belitung Archipelago Province.Identifying some geo-disaster potential, in order that the geo-disaster mappingcaused by tin mining activity is done. The research is done by observinggeological, geomorphological, erosion dan sedimentation conditions, massmovement, abrasion, dan floods. Geo-disaster potential is ilustratrated in map asresult of work using geographic information system (GIS) software. Geodisastersthat come from tin mining at study area are erosion, sedimentation,mass movement, floods and abrasion on the beach, which is about 67% area.Keywords: Geo-disaster, Mapping, Mining, Potential.